Effects of experimental nephrosis on basement-membrane components and enzymes of collagen biosynthesis in rat kidney. - Jukkola, A (1985)
The aim of the present study was to find out whether the basement-membrane proteins laminin and type IV collagen are involved in the development of aminonucleoside-induced nephrosis. These proteins were measured by specific radioimmunoassays in serum, urine and kidney-cortex samples, and they were localized in the glomeruli by indirect immunofluorescence. Nephrosis was induced in rats with a single intraperitoneal injection of puromycin aminonucleoside. Serum laminin concentrations, detected by a radioimmunoassay for the P2 domain of the protein, increased to reach a maximum at days 5-7, and they remained elevated until at least day 14. The increase preceded the development of proteinuria, suggesting a role for laminin in glomerular function. Concomitant with proteinuria, increasing amounts of laminin antigenicity were also found in the urine. The size of the laminin antigen in serum was estimated by gel filtration, and the serum forms were found to contain both the P1 and the P2 regions of the intact laminin molecule. On the other hand, there were no changes in the serum or urinary concentrations of type-IV-collagen-derived antigens, as detected by a radioimmunoassay for the 7S collagen domain of this protein. The total content of laminin in kidney cortex, measured after digestion of the tissue with trypsin and collagenase, was, at day 9, still comparable with normal values, and the distribution of both basement-membrane proteins in the glomeruli, studied by indirect immunofluorescence, was similar to that in the controls. The tissue damage induced by aminonucleoside, however, seems to stimulate collagen biosynthesis, as the activities of prolyl 4-hydroxylase, lysyl hydroxylase and galactosylhydroxylysyl glucosyltransferase in kidney tissue increased significantly, with maxima at days 8-10.